Organisational Climate as a Driver of Employee Performance: The Case of Naftal Company Tlemcen⁠ in Algeria - Belbachir, Wafa Ahmed; Assia Brahimi (Naše gospodarstvo/Our economy, 2026)
This study aims to highlight the impact of organisational climate, with its dimensions represented by organisational structure, leadership style, communication pattern, teamwork, and incentive system, on employee performance ⁠ at Naftal Tlemcen Branch. To achieve its objectives⁠, the study adopted a descriptive-analytical approach based on a questionnaire with a sample of 200 valid responses, and the data were analysed using SPSS. The results revealed a strong and statistically significant relationship between the dimensions of organisational climate and employee performance, indicating that improving the organisational climate directly contributes to enhancing performance efficiency and strengthening human resource effectiveness. Furthermore, the findings emphasized that a clear organisational structure, a participatory leadership style, the development of communication channels, the promotion of teamwork culture, and a⁠ fair incentive system are fundamental elements for creating a positive work⁠ environment capable of achieving the institution’s goals and improving employee productivity.
Keywords: Organisational climate; Employee performance; Work environment; Productivity; Naftal Tlemcen Company